No changes in the oxytocin system in alcohol-dependent female rodents and humans: towards a sex-specific psychopharmacology in alcoholism : commentary - Hansson, Anita C.; Spanagel, Rainer (Addiction biology, 2021)
A pronounced decrease of oxytocin and increase of oxytocin receptor binding sites were recently reported in male alcohol dependent rats and male alcohol dependent patients. Here we comment on this and emphasize that in female alcohol dependent rats and humans no changes occur in the oxytocin system. We therefore suggest specific intervention with oxytocin only in male subjects.
First published: 05 August 2020
Gesehen am 17.08.2021